Matching Mental Models: The starting point for authentic assessment in robotics - Edwards-Leis, Christine (Design and Technology Education: An International Journal, 2007)
This paper discusses the matches and mismatches that occur between the mental models held by the teacher and students undertaking a robotics activity in an Australian school. It proposes that an understanding of participants’ mental models of learning and assessment plays an important role in planning for, and reporting, on authentic assessment of a technology-based activity. The longitudinal project, over 20 months, was an empirical qualitative study centred within information processing theory and linked with the introspection mediating process tracing paradigm. It involved students and their teacher in a socio-economically diverse urban Australian primary school and aimed to establish how the identification of participants’ mental models can assist in the authentic assessment of learning through a richer understanding of the cognitive development taking place in a technology based learning experience.Robotics, as a component of the Queensland Technology Years 1 to 10 Syllabus published in 2003, provides a rich, multi-disciplinary environment in which to engage middle years students in Australia. The syllabus document provides guidance on planning and assessment for design and technology activities and provides a specific module for robotics. However, engagement is not enough to ensure learning. All participants, students or teachers, bring to such activities their own mental models of robotics, learning, and assessment. Can understanding the matches and mismatches of such mental models provide a greater understanding of the individual’s learning journey and the suitable assessment practices required to map the journey? This paper explores the participants’ mental models at the halfway point of the project.